2017
DOI: 10.1097/nna.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Commitment to BSN Completion

Abstract: The 2010 Institute of Medicine's Future of Nursing report posed recommendations to increase numbers of nurses with baccalaureate degrees or greater to 80%. This project engaged associate degree nurses in motivational interviewing focusing on finding and removing barriers to baccalaureate matriculation and completion. Results indicated a statistically significant influence on attitudes and return-to-school decision making and identified a qualitative theme: "I know more now… I could be a better nurse."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…11 From 2010 to 2020, studies and reports from academic and legislative perspectives demonstrated active work supporting RN-to-BSN academic progression [12][13][14][15][16] ; however, limited studies were published on healthcare organizations' strategies and nursing school partnerships to influence progression. These studies revealed several themes including attitudes and beliefs of non-BSN RNs, 17,18 professional growth and development, 19 organizational support for nursing advancement, 20 motivators and barriers, [21][22][23][24][25] leadership engagement, 26 and chief nurse executive (CNE) drivers. 27 The research reinforces 4 imperatives: 1) linkage of care delivery by baccalaureate-prepared RNs to improved patient outcomes; 2) the importance of explaining the "why" of academic progression to RNs and organizational leaders; 3) the importance of customizing the use and recognition of baccalaureate-prepared RNs within organizations; and 4) the accountability CNEs have for removing nurses' barriers to access and succeed in RN-to-BSN programs.…”
mentioning
confidence: 99%
“…11 From 2010 to 2020, studies and reports from academic and legislative perspectives demonstrated active work supporting RN-to-BSN academic progression [12][13][14][15][16] ; however, limited studies were published on healthcare organizations' strategies and nursing school partnerships to influence progression. These studies revealed several themes including attitudes and beliefs of non-BSN RNs, 17,18 professional growth and development, 19 organizational support for nursing advancement, 20 motivators and barriers, [21][22][23][24][25] leadership engagement, 26 and chief nurse executive (CNE) drivers. 27 The research reinforces 4 imperatives: 1) linkage of care delivery by baccalaureate-prepared RNs to improved patient outcomes; 2) the importance of explaining the "why" of academic progression to RNs and organizational leaders; 3) the importance of customizing the use and recognition of baccalaureate-prepared RNs within organizations; and 4) the accountability CNEs have for removing nurses' barriers to access and succeed in RN-to-BSN programs.…”
mentioning
confidence: 99%